Intentions to return of undocumented migrants: illegality as a cause of skill waste - Nicola D. Coniglio; Giuseppe De Arcangelis; Laura Serlenga (Institute for the Study of Labor (IZA), 2006)
In this paper we show that highly skilled undocumented migrants are more likely to return home than migrants with low or no skills when illegality causes skill waste, i.e. when illegality reduces the rate of return of individual capabilities (i.e. skills and human capital) in both the labor and the financial markets of the country of destination. This proposition is first illustrated in a simple life-cycle framework, where illegality acts as a tax on skills, and then is tested on a sample of apprehended immigrants that crossed unlawfully the Italian borders in 2003. The estimation confirms that the intention to return to the home country is more likely for highly skilled than low-skill illegal immigrants. The presence of migration networks in the destination country may lower the skill-waste effect. The empirical result of this paper contrasts with the common wisdom on return decisions of legal migrants, according to which low-skill individuals are more likely to go back home rather than highly skilled migrants.
urn:nbn:de:101:1-20090622325
Keywords: 330